Regional Economic Growth; Socio-Economic Disparities among Counties - SARICA, Salih Özgür (Journal of Economic Development, Environment and People, 2014)
State level economy has always been relying on its major metropolitan area’s economic success. So, such metropolitan agglomerations have been considered the only agents that can foster the state’s economic standing as if other economic places do (or may) not have significant contribution to the regional economy. In contrast, as some major cities enhance their economic well-being and agglomerate in specialized sector, the rest of the region lose their economic grounds or stay constant by widening the economic gap among cities. Therefore, an institutional approach can help to establish new regional arrangements to substitute all economic places to coordinate each other and succeed the economic growth as part of state government by reducing the disparities. In this sense, this study builds upon the inquiry that seeks the impacts of some economic disparities among economic places (counties) on the performances of state level regional economy.